Asuhan Kebidanan Komprehensif Pada Ny. N G1P0A0 Dengan Faktor Resiko Umur - Aryanti Musyarfah; Endang Susilowati; Mupliha Mupliha (Corona: Jurnal Ilmu Kesehatan Umum, Psikolog, Keperawatan dan Kebidanan, 2024)
Background: World Health Organization (WHO) in 2020 the maternal mortality rate (MMR) in the world is 152 deaths per 100,000 live births. In ASEAN, the highest MMR in 2020 is in Myanmar, which is 235 per 100,000 live births. The maternal mortality rate in Brebes Regency in 2020 was 62 cases. In the Bantarkawung Health Center working area in 2020 there was 1 case, in 2021 there were 5 cases. Objective: To provide comprehensive midwifery care services to Mrs. N Age 19 Years G1P0A0 with Risk Factors Age <20 Years at the Bantarkawung Health Center, Brebes Regency with a midwifery management approach according to Varney's seven steps and SOAP. Research method: This study uses descriptive qualitative research with a case study design. The Scientific Writing assignment report is written based on a case report of comprehensive midwifery care in pregnant women, childbirth, newborns, and postpartum using the type of case review study research method. Results: The results of comprehensive midwifery care are the absence of gaps between theory and practice where according to the theory pregnant women with a young age <20 years will experience several risks such as in any.N who experienced a short TFU of 28 cm. Conclusion: After conducting an assessment and collecting data on comprehensive midwifery care on Mrs. N with risk factors for age <20 years at the puskesmas from third trimester pregnancy.